Fluorescence studies of nicotinic acetylcholine receptor and its associated lipid milieu: The influence of Erwin London's methodological approaches - Barrantes, Francisco José (2022)
Fil: Barrantes, Francisco José. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina